Production Shock Phenomenon: An Overview of (Scomberoides sp; Megalaspis sp; and Decapterus sp) Production in Sunda Strait-Indonesia - Boimin, Boimin (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2024)
In the last decade, fishery production has decreased (production shock) due to causes such as excess effort, climate change, and implications of inappropriate policies. The consequences of the policy also increase the risk and vulnerability of fish stocks and affect food security. This research was conducted in the Sunda-Indonesia Strait in 2019 using production data, efforts, and the results of interviews with fishers in Lempasing Landing Port-Lampung. The analysis carried out included the CPUE trend as an indicator of productivity, MSY analysis, and prediction models of changes in effort patterns in 3 species of Decapterus, Scomberoides, and Megalaspis sp. The results obtained during 2010-2019 show that the three fish species' production has decreased, including efforts. Efforts to catch Decapterus decreased 27.3% per year, Scomberoide decreased efforts by 18.8% per year, and Megalaspis decreased rates of efforts by 14.32% per year. The productivity assessed from CPUE appears to be increasing, which is influenced by a decrease in the effort. Stock potential with the three species' Fox model shows an under fishing status, which means the high stock or low effort. The production that decreases during under fishing indicates a production shock due to reduced fish stocks or decreased fishing capacity. The potential for production shock can increase due to natural disasters and inappropriate policies.